2013
DOI: 10.1111/ecc.12065
|View full text |Cite
|
Sign up to set email alerts
|

A phase II open-label study of the intravenous administration of homoharringtonine in the treatment of myelodysplastic syndrome

Abstract: Homoharringtonine is an alkaloid inhibitor of protein synthesis with activity in myeloid malignancies. We report a phase II pilot study of homoharringtonine in myelodysplastic syndrome (MDS). Induction consisted of homoharringtonine at 2.5 mg/m2 via continuous infusion for seven days. Maintenance was given every 4 weeks. Nine patients were enrolled: five with refractory anaemia with excess blasts, two with refractory anaemia with excess blasts in transformation, one each with refractory anaemia and chronic mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The current study has demonstrated that cytogenetic and molecular abnormalities were able to affect AML induction therapy, RFS and OS, as well as being potential effective prognostic factors (41,42). In low-risk patients, the CR rates of the HCE and IA groups were 84.6 and 95.8%, respectively, and there was no significant difference between these groups.…”
Section: Discussionmentioning
confidence: 66%
“…The current study has demonstrated that cytogenetic and molecular abnormalities were able to affect AML induction therapy, RFS and OS, as well as being potential effective prognostic factors (41,42). In low-risk patients, the CR rates of the HCE and IA groups were 84.6 and 95.8%, respectively, and there was no significant difference between these groups.…”
Section: Discussionmentioning
confidence: 66%
“…HHT has also been administered to adults with MDS (7,12,(31)(32)(33). Daver et al (31) reported that the CR rate was 11% in patients with intermediate and high risk MDS, who received HHT alone.…”
Section: Discussionmentioning
confidence: 99%
“…HHT has also been administered to adults with MDS (7,12,(31)(32)(33). Daver et al (31) reported that the CR rate was 11% in patients with intermediate and high risk MDS, who received HHT alone. In addition, combination therapy of HHT and low-dose AraC has been demonstrated to be an effective strategy for advanced MDS and RAEBt and CR was observed in 46.9% (32); however, the median OS was shorter (18.2 months).…”
Section: Discussionmentioning
confidence: 99%
“…In another Phase II pilot study of HHT in myelodysplastic syndrome, HHT was given at a dose of 2.5 mg/m 2 via continuous infusion for 7 days and maintenance every 4 weeks. One patient (11%) responded with a CHR and cytogenetic remission after one course and eight patients did not respond 74. Similarly, the effect of omacetaxine mepesuccinate was tested in patients with acute myeloid leukemia.…”
Section: Efficacy Studiesmentioning
confidence: 99%